Cara Praktis Penentuan Uji Statistik dalam Penelitian Kesehatan dan Kedokteran - Dr. Stang, Drs, M.Kes (Mitra Wacana Media, 2014)
Cara Praktis Penentuan Uji Statistik dalam Penelitian Kesehatan dan Kedokteran